Intestinal Microbiota and Allergy. Probiotics and Prebiotics in Prevention and Treatment of Allergic Diseases - Svetlana G. Makarova; Leyla S. Namazova-Baranova; Oksana A. Ereshko; Dmitry S. Yasakov; Pavel E. Sadchikov (Педиатрическая фармакология)
Intestinal microbiota is the factor that identifies considerably the human health. The impact of the microbial factor on a child begins long before his birth. Children have certain features in forming of immune response and intestinal microbiocenosis even before birth. Decline in diversity of intestinal microbiota is common in children with allergic disease even during first months of life, before allergic pathology development. Capabilities for microbiota development adjustment are sufficiently restricted. However it is clinically proven that early (within the first hours of life) breastfeeding attachment, breastfeeding itself within at least first 6 months of life, the use of prebiotics in milk formulas as well as the use of probiotics can give positive results on allergy management. In this review we present results of recent metaanalyses and consensus papers of international medical communities about use of probiotics and prebiotics in prevention and treatment of allergic diseases. Despite great scientific and practical interest to this topic, authors of metaanalyses bring our attention to the lack of evidence-based clinical trials.